Virus-Mediated Compartmentalization of the Host Translational Machinery - Desmet, Emily A. (American Society of Microbiology, 2014)
Viruses require the host translational apparatus to synthesize viral proteins. Host stress response mechanisms that suppress translation, therefore, represent a significant obstacle that viruses must overcome. Here, we report a strategy whereby the mammalian orthoreoviruses compartmentalize the translational machinery within virus-induced inclusions known as viral factories (VF). VF are the sites of reovirus replication and assembly but were thought not to contain ribosomes. It was assumed viral mRNAs exited the VF to undergo translation by the cellular machinery, and proteins reentered the factory to participate in assembly. Here, we used ribopuromycylation to visualize active translation in infected cells. These studies revealed that active translation occurs within VF and that ribosomal subunits and proteins required for translation initiation, elongation, termination, and recycling localize to the factory. Interestingly, we observed components of the 43S preinitiation complex (PIC) concentrating primarily at factory margins, suggesting a spatial and/or dynamic organization of translation within the VF. Similarly, the viral single-stranded RNA binding protein σNS localized to the factory margins and had a tubulovesicular staining pattern that extended a short distance from the margins of the factories and colocalized with endoplasmic reticulum (ER) markers. Consistent with these colocalization studies, σNS was found to associate with both eukaryotic translation initiation factor 3 subunit A (eIF3A) and the ribosomal subunit pS6R. Together, these findings indicate that σNS functions to recruit 43S PIC machinery to the primary site of viral translation within the viral factory. Pathogen-mediated compartmentalization of the translational apparatus provides a novel mechanism by which viruses might avoid host translational suppression.